Botswana : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Botswana. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that sizable buffers and prudent policies have kept Botswana's economy stable despite diamond market weakness and volatility. In 2017, despite higher diamond production, real GDP growth dropped to 2.4 percent primarily because of the closure of a major copper and nickel mining company. Non-mineral growth decelerated reflecting the indirect effects of the company's closure on electricity and transportation, coupled with a small slowdown in trade and construction. In 2018-2019, it is expected that improving conditions in the diamond market and fiscal stimulus will temporarily boost economic activity. The medium-term economic outlook will depend heavily on the successful implementation of critical structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet